Analisis Peran Aktivitas Pelabuhan Sri Bintan Pura terhadap Pertumbuhan UMKM di Sekitar Kawasan Pelabuhan - Nor Syakina; Ibaniyah; Rasmi Delmita Samongilaila (CV. ITTC INDONESIA, 2025)
This study analyzes the role of economic activities at Sri Bintan Pura Port in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in the surrounding area. As the main passenger and logistics hub in Tanjungpinang, the port generates significant mobility that creates market opportunities, strengthens local supply chains, and stimulates the emergence of new businesses. Using a literature study approach, this research synthesizes empirical findings related to the port’s economic linkages, MSME development, and factors that influence their performance. The results show that the port contributes to MSME growth through increased passenger flows, improved logistics efficiency, and expanded market access—including tourism-based markets. However, several constraints remain, including limited infrastructure, weak regulatory support, insufficient partnerships, and constrained access to capital and digital skills. These challenges hinder MSMEs from fully optimizing the economic potential of the port. The study recommends integrated policy strategies such as formal business space allocation, CSR-based port–MSME partnerships, digital marketing initiatives, tourism-port development, and MSME-friendly logistics services. Strengthening these strategies can enhance inclusive and sustainable local economic development driven by Sri Bintan Pura Port.